ANALISA PENGGUNAAN PASIR PANTAI PECAK LUMAJANG SEBAGAI PENGGANTI AGREGAT HALUS TERHADAP KUAT TEKAN (Fakultas Teknik Universitas Wisnuwardhana, 2023)
One of the determinants of the quality of concrete is the quality of fine aggregate used as a concrete mix because most of the concrete volume is filled with fine aggregate. The fine aggregate quality observed in this research was beach sand at Watu Pecak in Lumajang. This study aims to determine how much the compressive strength of the concrete has using river sand ex. Lumajang, using unwashed beach sand, and beach sand washed with fresh water against a concrete compressive strength of 30 MPa with the same proportion of each sand. Concrete samples using a cylinder diameter of 15 cm and height of 30 cm amounted to 27 pieces of the test sample. Concrete age will be tested in 7 (seven) days, 14 (fourteen) days, and 28 (twenty-eight) days. The average concrete compressive strength results using washed beach sand is 31,93 Mpa. The value is 1,66 Mpa or 4,9% smaller than normal concrete, which equals 33,59 Mpa. The average concrete compressive strength using unwashed beach sand is 31,58 Mpa. The value is 2,01 Mpa or 6,29% smaller than normal concrete and is 0,35 or 1,11% smaller than concrete using washed beach sand.